2017
DOI: 10.22159/ajpcr.2017.v10i5.17749
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Rheumatoid Arthritis and Health-Related Quality of Life in Korean Women Aged 50 Years and Over

Abstract: Objective: The purpose of this study is to evaluate the association between rheumatoid arthritis (RA) and health-related quality of life (HRQoL) in Korean women.Methods: Participants (n=2068) aged 50 years or older were selected from Korea National Health and Nutrition Examination Survey (KNHANES) [2005][2006][2007][2008]. Sociodemographic characteristics, medical history of RA, and EuroQol-5 dimension were obtained from the KNHANES dataset. Results:The results revealed that demographic variables, including ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 14 publications
2
7
0
Order By: Relevance
“…According to our findings, the responses from the utility score and the WTP values were consistent with prior expectations [18,21]. For each scenario, the utility associated with the more severe health states was lower than that of the less severe health states.…”
Section: Reliabilitysupporting
confidence: 84%
“…According to our findings, the responses from the utility score and the WTP values were consistent with prior expectations [18,21]. For each scenario, the utility associated with the more severe health states was lower than that of the less severe health states.…”
Section: Reliabilitysupporting
confidence: 84%
“…Thirty‐one studies reported utility scores of RA patients 22‐24,34‐42,45,47‐63,65 . The pooled mean EQ‐5D score was 0.66 (95% CI 0.63‐0.69) with high heterogeneity I 2 = 99.65% (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-one studies reported utility scores of RA patie nts. [22][23][24][34][35][36][37][38][39][40][41][42]45,[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]65 The pooled mean EQ-5D score was 0.66 (95% CI 0.63-0.69) with high heterogeneity I 2 = 99.65% (Figure 2A).…”
Section: Overall Pooling Of Eq-5dmentioning
confidence: 99%
“…Examination included general physical examination along with cardiovascular systemic examination and local knee examination. Orthopaedic evaluation was done using K-L grading 10 and CV risk was determined using the JBS3 CV risk score calculator. 15 Fasting blood sample was collected to know the levels of their serum total cholesterol and serum high density lipoprotein.…”
Section: Methodsmentioning
confidence: 99%
“…Patients diagnosed with knee osteoarthritis (Kellgren and Lawrence (KL) grade ≥2 on knee X-ray 9 ) and ≥50 years old 10 were invited to take part. The KL grading system is as follows:…”
Section: Study Participantsmentioning
confidence: 99%